Graphene-oxide-wrapped ZnMn2O4 as a high performance lithium-ion battery anode. (23rd October 2017) - Sun, Qian; Bijelić, Mirjana; Djurišić, Aleksandra B; Suchomski, Christian; Liu, Xiang; Xie, Maohai; Ng, Alan M C; Kong Li, Hang; Shih, Kaimin; Burazer, Sanja; Skoko, Željko; Djerdj, Igor; et al.
Abstract: Cation distribution between tetrahedral and octahedral sites within the ZnMn2 O4 spinel lattice, along with microstructural features, is affected greatly by the temperature of heat treatment. Inversion parameters can easily be tuned, from 5%–19%, depending on the annealing temperature. The upper limit of inversion is found for T = 400 °C as confirmed by x-ray powder diffraction and Raman spectroscopy. Excellent battery behavior is found for samples annealed at lower temperatures; after 500 cycles the specific capacity for as-prepared ZnMn2 O4 is 909 mAh g −1, while ZnMn2 O4 heat-treated at 300 °C is 1179 mAh g −1, which amounts to 101% of its initial capacity. Despite the excellent performance of a sample processed at 300 °C at lower charge/discharge rates (100 mAh g −1 ), a drop in the specific capacity is observed with rate increase. This issue is solved by graphene-oxide wrapping: the specific capacity obtained after the 400th cycle for graphene-oxide-wrapped ZnMn2 O4 heat-treated at 300 °C is 799 mAh g −1 at a charge/discharge rate 0.5 A g −1, which is higher by a factor of 6 compared to samples without graphene -oxide wrapping.